Increasing Skills in Writing Literature Study on Research-Based Learning Through Authentical Assessment Lecturing in Innovation Class of Social Science Learning - Wardani, Naniek Sulistya (International Journal of Active Learning, 2017)
The purpose of this study is to determine whether the improvement of literature review skills on research-based learning can be pursued through the authentic assessment of the lectures of the Innovation of Learning IPS of PGSD students. This type of research is a classroom action research, using a spiral model of C. Kemmis and Robin Mc. Taggart. The research procedure uses 2 cycles, each cycle consists of 3 stages namely, 1) action planning 2) implementation of action and observation, 3) reflection. The subjects of the study were all students of PGSD Class 2014 E of the subjects of Innovation of IPS Learning as much as 27 students consisting of 7 male students and 20 female students. Data collection techniques use observation and product assessment. Data analysis technique is a percentage technique that compares literacy review writing skills through authentic assessment in IPS lectures between cycles. The result of the research shows that there is an improvement of writing skill of study lecture study of IPS learning innovation, which is pursued through authentic assessment. This is evident from the improvement of writing skills worthy of achievement from cycle 1 to cycle 2 ie from 62.14% of 27 students increased to 72.60% of all students in cycle 2. Writing skills in research-based learning is a skill to express the idea of the problem , Organizing facts, concepts and principles, use of EYD grammar and grammar. Authentic assessment is an assessment consisting of connection aspects, reflection aspects, and feedback aspects